"The challenges made me stronger": What contributes to young people's resilience in Ethiopia? - Crivello, G; Tiumelissan, A; Heissler, K (Young Lives, 2021)
This working paper explores the meanings and experiences of resilience, and its gender dimensions, among a cohort of Ethiopian children exposed to poverty and adversity across the early life course. It asks why some girls and some boys seem to fare well as they transition to adulthood, despite the challenges and obstacles they had faced, while others do less well.